Strategi Pemasaran Syariah dalam Meningkatkan Jumlah Pendapatan di Toko Istana Beauty Ganding, Sumenep - Ais Faisetul Imamah; Anna Zakiyah Hastriana (Alkasb: Journal of Islamic Economics, 2022)
The sharia marketing strategy carried out by Toko Istana Beauty involves selecting and formulating the main target market. This is done by using a marketing mix strategy consisting of product, price, place and promotion. This research aims to analyze the impact of implementing sharia marketing strategies at the Istana Beauty Store in increasing revenue, and the extent to which the sharia marketing strategy implemented by the Istana Beauty store is able to attract new buyers and retain existing customers. This type of research is field research, namely research by going directly into the field and making direct observations involving researchers at the research location. The marketing mix strategy implemented includes: Product strategy by implementing product diversity, product quality and always collecting the newest products, pricing strategy by setting standard product prices and in accordance with the quality of the product, location strategy, namely choosing a strategic place and easy to reach. consumer. Promotion strategies using social media include WhatsApp, Facebook, Tiktok, and using distribution channels directly to consumers through online and offline sales. The impact of implementing this sharia marketing strategy was felt by Toko Istana Beauty, this was proven by achieving the target revenue of IDR 204,604,000. With an average of Rp. 40,921,800. although the results showed that the income obtained by the Istana Beauty Shop was relatively fluctuating.